![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A, (2x+1)3=343
=> (2x+1)3=73
=> 2x + 1 = 7
=> 2x = 6
=> x = 3
B, 2x+2x+3=144
=> 2x+2x . 23 =144
=> 2x ( 1 + 23 ) =144
=> 2x ( 1 + 8 ) =144
=> 2x . 9 =144
=> 2 x = 16
=> 2 x = 2 4
=> x = 4
C, 3x+3x+2=2430
=> 3x+3x . 32 =2430
=> 3x . ( 1 + 32 ) =2430
=> 3x . ( 1 + 9 ) =2430
=> 3x . 10 =2430
=> 3x = 243
=> 3x = 3 5
=> x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x+1=7^{542}.7^{543}\)
\(x+1=7^{1085}\)
\(x=7^{1085}-1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3^{x+2}+3^x=2430\)
\(\Rightarrow3^x\cdot\left(9+1\right)=2430\)
\(\Rightarrow3^x=2430:10=243\)
\(\Rightarrow3^x=3^5\)
\(\Rightarrow x=5\)
ti ck nha
²⁴ʱ๖ۣۜSυρɾεмε...
3^{x+2}+3^x=24303x+2+3x=2430
\Rightarrow3^x\cdot\left(9+1\right)=2430⇒3x⋅(9+1)=2430
\Rightarrow3^x=2430:10=243⇒3x=2430:10=243
\Rightarrow3^x=3^5⇒3x=35
\Rightarrow x=5⇒x=5
![](https://rs.olm.vn/images/avt/0.png?1311)
a)...
b)9^x-1=9
=>9^x-1=9^1
=>x-1=1
=>x=1+1
=>x=2
c)x^4=16
=>x^4=2^4
=>x=2
d)2^x:2^5=1
=>2^x=1.2^5
=>2^x=2^5
=>x=5
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)3-\left(17-x\right)=-24+12\)
\(\Leftrightarrow3-17+x=-12\)
\(\Leftrightarrow-14+x=-12\)
\(\Leftrightarrow x=-12+14=2\)
a) 3 - (17 - x) = -24 + 12
=> 3 - 17 + x = -12
=> -14 + x = -12
=> x = -12 + 14
=> x = 2
b) -5 + (16 - x) = 22.3 - 52
=> -5 + 16 - x = 12 - 25
=> 11 - x = -13
=> x = 11 + 13
=> x = 24
c) -26 - (x - 7) = 34 - 92
=> -26 - x + 7 = 81 - 81
=> -19 - x = 0
=> x = -19 - 0
=> x = -19
d) -36 - (4 - x) = 37 + (-5)
=> -36 - 4 + x = 32
=> -40 + x = 32
=> x = 32 + 40
=> x = 72
![](https://rs.olm.vn/images/avt/0.png?1311)
a,
(x-2)^3=-27
<=>(x-2)^3=-3^3
<=>x-2=-3
<=>x=-1
vậy .....
b,
3(x+2)^4=48
<=>(x+2)^4=16
<=>(x+2)^4=2^4=(-2)^4
<=>\(\orbr{\begin{cases}x+2=2\\x+2=-2\end{cases}< =>\orbr{\begin{cases}x=0\\x=-4\end{cases}}}\)
vậy ..........
a ) Ta có : \(\left(x-2\right)^3=-27\)
\(\Rightarrow\left(x-2\right)^3=\left(-3\right)^3\)
\(\Rightarrow x-2=-3\)
\(\Rightarrow x=-3+2\)
\(\Rightarrow x=-1\)
Vậy \(x=-1\)
b) Ta có : \(3.\left(x+2\right)^4=48\)
\(\Rightarrow\left(x+2\right)^4=16\)
\(\Rightarrow\orbr{\begin{cases}\left(x+2\right)^4=2^4\\\left(x+2\right)^4=\left(-2\right)^4\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x+2=2\\x+2=-2\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=-4\end{cases}}\)
Vậy \(x=0;x=-4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a, 96 \(⋮x=>x\inư\left(96\right)\)
b, \(2^x.15+2^x.17=4^{30}\)
\(2^x\left(15+17\right)=4^{30}\)
\(2^x.32=4^{30}\)
\(2^x.2^5=2^{60}\)
\(2^x=2^{60}:2^5\)
\(2^x=2^{55}\)
=> x = 55
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a, \(\left(3x-1\right)^3=27=3^3\)
\(\Rightarrow3x-1=3\Rightarrow3x=4\Rightarrow x=\dfrac{4}{3}\)
b, \(2^{x-2}=16=2^{4^{ }}\)
\(\Rightarrow x-2=4\Rightarrow x=6\)
c, \(3^x=9.27=3^2.3^3=3^5\)
\(\Rightarrow x=5\)
d, \(15x-899:29=194\)
\(15x-31=194\Rightarrow15x=225\Rightarrow x=15\)
Bài 2:
a, \(5^2.3^2-32:2^{2^{ }}\)\(=15^2-2^5:2^2=225-8=217\)
b, \(19.37+63.19-400\)\(=19.\left(37+63\right)-400=19.100-100.4=100.\left(19-4\right)\)
\(=100.15=1500\)
c, 205-\(\left\{102-\left[48-\left(16-14\right)^{ }3\right]\right\}\)\(=205-\left\{102-\left[48-2^3\right]\right\}=205-\left(102-40\right)\)
\(=205-62=143\)
\(2^x+2^{x+1}=48\)
\(2^x.1+2^x.2^1=48\)
\(2^x\left(1+2\right)=48\)
\(2^x.3=48\)
\(2^x=16\)
\(2^x=2^4\)
\(\Rightarrow x=4\)
Vậy x = 4
\(a,\text{ }2^x+2^{x+1}=48\)
\(2^x\cdot\left(1+2\right)=48\)
\(2^x=48\text{ : }3\)
\(2^x=16\)
\(2^x=2^4\)
\(\Rightarrow\text{ }x=4\)